2012
DOI: 10.2217/epi.12.25
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation in Schizophrenia Subjects: Gender and MTHFR 677C/T Genotype Differences

Abstract: Aim In schizophrenia, metabolic syndrome incidence is double that of the general population, with women having a higher incidence. Pharmacogenetically regulated folic acid may be related to this risk. DNA methylation and metabolic syndrome within this group has not been previously studied. Methods Metabolic syndrome was evaluated with fasting laboratory measurements, and dietary and lifestyle assessments. Methylation analysis used a peripheral sample for the LINE-1 assay. DNA was also genotyped for MTHFR 677… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
4
33
1
Order By: Relevance
“…MTHFR-mediated methylation may contribute towards the onset of AIWG [73]. Previous studies have found evidence of an association between AIWG/antipsychotic-induced metabolic syndrome and rs1801131 [72,74], whereas we found a nominal association between weight gain and rs17367504 (only 8 kbp from rs1801131) in the SGAP-treated group and rs1133398 (40 kbp from rs1801131) both in the MS-treated group and in the combined-treatment group.…”
Section: Main Findingscontrasting
confidence: 77%
“…MTHFR-mediated methylation may contribute towards the onset of AIWG [73]. Previous studies have found evidence of an association between AIWG/antipsychotic-induced metabolic syndrome and rs1801131 [72,74], whereas we found a nominal association between weight gain and rs17367504 (only 8 kbp from rs1801131) in the SGAP-treated group and rs1133398 (40 kbp from rs1801131) both in the MS-treated group and in the combined-treatment group.…”
Section: Main Findingscontrasting
confidence: 77%
“…Furthermore, increasing evidence has been showing that epigenetic mechanisms are involved in age-related traits and in gender differences. For instance, DNA methylation has been associated with particular genotypes in the female group in a study of schizophrenia 27. There is now a consensus that studies should focus on epigenetic biomarkers and their interaction with DNA and environment 28.…”
Section: Discussionmentioning
confidence: 99%
“…Burghardt et al (2012) studied the MTHFR C677T (rs1801133) variant with Long Interspersed Nucleotide Element 1 (LINE-1) DNA methylation, an index of global methylation levels, in 133 patients with schizophrenic disorders. They reported a significant interaction between gender, MTHFR C677T genotype, and overall global methylation.…”
Section: Epigenetics and Aiwgmentioning
confidence: 99%
“…They reported a significant interaction between gender, MTHFR C677T genotype, and overall global methylation. Females who were homozygous for the T allele had the lowest methylation compared to other groups [58]. Another study by Lott et al (2013) analyzed the relationship between COMT promoter methylation and metabolic syndrome in 86 schizophrenia patients treated with atypical antipsychotics.…”
Section: Epigenetics and Aiwgmentioning
confidence: 99%